Ocular manifestations of trigeminal autonomic cephalgias: analysis of cases - V. V. Biloshytsky; V. A. Vasyuta; M. V. Biloshytska (Ukrainian Society of Ophthalmologists, 2021)
Trigeminal autonomic cephalgias (TACs) are the most common group of cephalgias with ocular symptoms and can be subdivided into cluster headache, paroxysmal hemicrania, short-lasting unilateral neuralgiform headache attacks and hemicrania continua. The diagnostic criterion at least one of the following autonomic symptoms or signs, ipsilateral to the headache: conjunctival injection and/or lacrimation; nasal congestion and/or rhinorrhoea; eyelid edema; forehead and facial sweating; forehead and facial ﬂushing; sensation of fullness in the ear; and miosis and/or ptosis. Symptoms of sympathetic blockade (ptosis, myosis, Horner's syndrome) may be present. Another characteristic that TACs share is periorbital or retroorbital location of headache pain. The cases of TACs reported demonstrate potential diagnostic pitfalls and patterns of ocular symptoms and treatment of these diseases. These patients not uncommonly present to ophthalmologists. Paying close attention to autonomic symptoms during history collection and meticulous elucidation of headache characteristics will facilitate a diagnosis and first-line treatment decisions.